Sistem Informasi Pemesanan Produk Teh Menggunakan Midtrans Payment Gateway Berbasis Android - Haerani, Sintia; Fakhriza, M. (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Currently, the system of marketing and product promotion via the internet is experiencing rapid growth. Many companies use information technology as a corporate strategy to provide products to all consumers without limiting space and time. From large companies to small and medium businesses have made online sales systems as cheap and affordable promotional facilities. With advances in technology, business people can certainly take advantage and minimize the impact that will occur. Tea garden factories can use consumers' smartphones to order products and payments directly from the application, making it easier and shorter the waiting time for consumers. Tea plantation factories can also cooperate with Midtrans as a third-party payment gateway in transactions with their consumers. The factory can also control the flow of transactions and revenue volume on the Midtrans website in real time without having to wait for employees to make daily bookkeeping. The development method used is the RAD method. The goal is to minimize existing problems and better maintain the safety of consumers.